THE LEUKOCYTE PROFILE OF ETAWA BREED GOATS SUFFERING FROM SUBCLINICAL MASTITIS IN SUKAWATI DISTRICT, GIANYAR BALI - Chitra Dwi Wulandari; Anak Agung Sagung Kendran; Romy Muhammad Dary Mufa (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Subclinical mastitis is a condition of mammary gland inflammation that often occurs in dairy goats without obvious symptoms. White blood cell examination is an important indicator in assessing the body's immune response and can help establish a diagnosis or animal health status. This study aims to determine changes in total and differential leukocytes in goats suffering from subclinical mastitis. Blood samples were taken from the jugular vein, then white blood cells were counted using a Hematology Analyzer and identified using the blood smear method. The data obtained were then analyzed descriptively including the total number of leukocytes and the number of leukocyte types. The results showed varying changes in the number and type of white blood cells, especially an increase in neutrophils and monocytes in peranakan etawa goats suffering from subclinical mastitis. For the total leukocytes of the five samples were 6.9 - 13.3 x 103/µL and for leukocyte differential, the total lymphocytes were 2.96 - 5.54 x 103/µL, Monocytes 0.20 - 0.66 x 103 /µL, Neutrophils 3.17 - 7.71 x 103/µL, Eosinophils 0 - 0.66 x 103/µL, and Basophils 0.